A Pathophysiological Aspect Of Asthi-Majjakshaya W.S.R. To Osteoporosis - Gill, Gurpreet Kaur; Yadav, Chhaju Ram; Yadav, Sarika (International Research Journal of Ayurveda & Yoga, 2020)
Nearly 1 million folks annually report taking time away from work to treat and recover from musculoskeletal pain or loss of function due to overexertion. Osteoporosis is a major and emerging health problem worldwide. It affects an estimated 75 million people in United States, Europe and Japan combined. Osteoporosis is a disease that is characterized by low bone mass, deterioration of bone tissue, and disruption of bone microarchitecture: it can lead to compromised bone strength and an increase in the risk of fractures. There is no actual or relevant clinical entity mentioned in classics which can be correlated with osteoporosis term coined by contemporary science. In Ayurveda, Asthikshaya and Asthisaushirya may be discussed in this regard. The etiological factors for Asthikshaya and Asthisaushirya are assessed on the principles of Ashrayashrayi Bhava and in context of Majjakshaya. According to Ashrayashrayi Bhava, Asthi Dhatu is the seat of Vata Dosha and Asthi & Vata are inversely proportional to each other regarding increase and decrease. Increase of Vata leads to decrease of Asthi, therefore causes Asthikshaya. Asthisaushirya is not mentioned as a separate condition however as a symptom of Majjakshaya. Majjakshaya may take place after Asthikshaya as per the basic principles of Anulomakshaya. Since there is decrease of bone tissue in both the conditions, i.e., osteopenia and osteoporosis, it can be considered as Asthi-Majjakshaya attributable to its core of pathogenesis: 1) degeneration of bone tissue and 2) vitiation of Vata, the classical aspects of Asthi Majjakshaya can be implemented in the disease osteoporosis.